Functional recA, lexA, umuD, umuC, polA, and polB genes are not required for the Escherichia coli UVM response. - Palejwala, V A (1995)
The Escherichia coli UVM response is a recently described phenomenon in which pretreatment of cells with DNA-damaging agents such as UV or alkylating agents significantly enhances mutation fixation at a model mutagenic lesion (3,N4-ethenocytosine; epsilon C) borne on a transfected M13 single-stranded DNA genome. Since UVM is observed in delta recA cells in which SOS induction should not occur, UVM may represent a novel, SOS-independent, inducible response. Here, we have addressed two specific hypothetical mechanisms for UVM: (i) UVM results from a recA-independent pathway for the induction of SOS genes thought to play a role in induced mutagenesis, and (ii) UVM results from a polymerase switch in which M13 replication in treated cells is carried out by DNA polymerase I (or DNA polymerase II) instead of DNA polymerase III. To address these hypotheses, E. coli cells with known defects in recA, lexA, umuDC, polA, or polB were treated with UV or 1-methyl-3-nitro-1-nitrosoguanidine before transfection of M13 single-stranded DNA bearing a site-specific ethenocytosine lesion. Survival of the transfected DNA was measured as transfection efficiency, and mutagenesis at the epsilon C residue was analyzed by a quantitative multiplex DNA sequencing technology. Our results show that UVM is observable in delta recA cells, in lexA3 (noninducible SOS repressor) cells, in LexA-overproducing cells, and in delta umuDC cells. Furthermore, our data show that UVM induction occurs in the absence of detectable induction of dinD, an SOS gene. These results make it unlikely that UVM results from a recA-independent alternative induction pathway for SOS gene.